2016
DOI: 10.1002/cncr.29938
|View full text |Cite
|
Sign up to set email alerts
|

Increase in primary surgical treatment of T1 and T2 oropharyngeal squamous cell carcinoma and rates of adverse pathologic features: National Cancer Data Base

Abstract: Background There has been increasing interest in primary surgical treatment of patients with early T classification (T1–T2) oropharyngeal squamous cell carcinoma (OPSCC), with the stated goal of de-escalating or avoiding adjuvant treatment. We sought to determine the degree to which this interest has translated into changes in practice patterns, and the rates of adverse post-operative pathologic features. Methods Patients with T1–T2 OPSCC in the National Cancer Database (NCDB) treated from 2004–2013 were cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
148
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 22 publications
0
148
0
1
Order By: Relevance
“…31 High rates of adjuvant chemoradiotherapy are attributable to the elevated incidence of nodal metastases and extracapsular spread in HPV-positive pathologic specimens. 46,47 Extracapsular spread was originally identified as a poor prognostic indicator in two randomized controlled trials of advanced head and neck cancer that have made it an indication for adjuvant chemoradiotherapy under the current standard of care. 51 However, these studies were flawed because they grouped all head and neck subsites together, the majority of patients had OPSCC, and results were not stratified by HPV status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 High rates of adjuvant chemoradiotherapy are attributable to the elevated incidence of nodal metastases and extracapsular spread in HPV-positive pathologic specimens. 46,47 Extracapsular spread was originally identified as a poor prognostic indicator in two randomized controlled trials of advanced head and neck cancer that have made it an indication for adjuvant chemoradiotherapy under the current standard of care. 51 However, these studies were flawed because they grouped all head and neck subsites together, the majority of patients had OPSCC, and results were not stratified by HPV status.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of extracapsular spread in surgically treated OPSCC has been studied using the National Cancer and SEER databases and is estimated at 23% to 25%, increasing with higher N stages. 46,47 Recent retrospective studies by Sinha et al 48 and Maxwell et al 46 demonstrate that this feature does not negatively affect survival in HPV-positive OPSCC and may not require adjuvant chemoradiotherapy for successful treatment of this population. In 2013, the ADEPT (Adjuvant Deescalation, Extracapsular Spread, p16 Positive, Transoral) trial was launched to determine the benefit of chemotherapy in patients with HPV-positive OPSCC with extracapsular spread, using 2-year locoregional control and disease-free survival as end points.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…eHNS consists of a minimally-invasive procedure using miniaturized instrumentation that avoids mandibulotomy and external incisions. eHNS is performed with carbon dioxide laser microsurgery or robotic surgical system and has been associated with a resurgence of primary surgical treatment for T1-T2 OPC [16]. Early reports have demonstrated that eHNS is associated with a lower complication rate and faster post-operative recovery [17,18].…”
Section: Oropharynx Carcinoma Surgerymentioning
confidence: 99%
“…The introduction of transoral robotic surgery (tors)-which offers patients with newly diagnosed opscc an innovative alternative to the standard of treatment with rt, potentially providing superior functional outcomes-is currently being used for most patients with early opscc in the United States 2,3 . The uptake of tors is increasing despite a lack of clear evidence about its oncologic or quality-of-life outcomes 3,4 . A randomized trial is currently underway to evaluate those questions by directly comparing tors with rt 5 .…”
Section: Introductionmentioning
confidence: 99%